Probing diffusion laws within cellular membranes by Z-scan fluorescence correlation spectroscopy - Humpolícková, Jana; Gielen, Ellen; Benda, Ales; Fagulova, Veronika; Vercammen, Jo; Vandeven, Martin; Hof, Martin; Ameloot, Marcel; Engelborghs, Yves (Biophysical journal, 2006)
The plasma membrane of various mammalian cell types is heterogeneous in structure and may contain microdomains, which can impose constraints on the lateral diffusion of its constituents. Fluorescence correlation spectroscopy (FCS) can be used to investigate the dynamic properties of the plasma membrane of living cells. Very recently, Wawrezinieck et al. (Wawrezinieck, L., H. Rigneault, D. Marguet, and P. F. Lenne. 2005. Biophys. J. 89:4029-4042) described a method to probe the nature of the lateral microheterogeneities of the membrane by varying the beam size in the FCS instrument. The dependence of the width of the autocorrelation function at half-maximum, i.e., the diffusion time, on the transverse area of the confocal volume gives information on the nature of the imposed confinement. We describe an alternative approach that yields essentially the same information, and can readily be applied on commercial FCS instruments by measuring the diffusion time and the particle number at various relative positions of the cell membrane with respect to the waist of the laser beam, i.e., by performing a Z-scan.
Keywords: buněčná membrána; Spectrometry, Fluorescence; Humans; Microscopy, Confocal; biofyzika; fluorescenční spektrometrie; konfokální mikroskopie; lidé; lasery; Models, Statistical; difuze; biologický transport; Diffusion; nádorové buněčné linie; statistické modely; Biophysics; Cell Line, Tumor; Cell Membrane; Lasers; Biological Transport